The usability analysis of using augmented reality for linus students - Kamariah Awang; Syadiah Nor Wan Shamsuddin; Ismahafezi Ismail; Norkhairani Abdul Rawi; Maizan Mat Amin (Institute of Advanced Engineering and Science, 2019)
Mobile technology with Augmented Reality has become popular worldwide with a broad range of users, including students from all levels of education and the impact of mobile technology in classrooms has been extensively studied. This technology can be the source of motivation for LINUS students especially students with disabilities. The word usability also refers to the methods to improve the ease of use during a design process. Among the difficulties in teaching a LINUS student is the lack of visual media for understanding the subject especially in basic mathematics such as evaluating a number and calculating the number. The objective of the study was to evaluate the usability of using Augmented Reality in a mobile application among LINUS students in primary schools. This study used survey data gathered from 32 LINUS students of 3 different primary schools in Marang and Kuala Terengganu Districts. The questionnaire collected data on five construct of usability test to the LINUS students. The students used the mobile application while being guide by their teacher. They navigated all the buttons provided and answered the quiz too. The criteria of usability test consist of five constructs. The students showed a significant interest in learning numbers by actively participating in the LINUS sessions. The usability level was measured based on the five constructs. In summary, the augmented reality mobile application has a great potential to be used in teaching and learning, as in the Malaysia Education Development Plan 2013-2025 especially on the LINUS students.